2017
DOI: 10.6061/clinics/2017(01)09
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pharmacovigilance: multifaceted educational intervention related to the knowledge, skills and attitudes of multidisciplinary hospital staff

Abstract: OBJECTIVES:Most educational interventions in pharmacovigilance are designed to encourage physicians to report adverse drug reactions. However, multidisciplinary teams may play an important role in reporting drug-related problems. This study assessed the impact of a multifaceted educational intervention in pharmacovigilance on the knowledge, skills and attitudes of hospital professionals.METHOD:This prospective, open-label, non-randomized study was performed in a medium-complexity hospital in São Paulo, Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
8
41
0
6
Order By: Relevance
“…These suggestions made by participants were almost similar to other studies in different hospitals in the world [25,30,38]. These suggestions were almost similar to other studies conducted in other countries which show that educational interventions and other activities help to encourage ADR reporting increase awareness to ADRs and then increase the reporting rates of ADRs [20,21,25,30,38,[43][44][45]. Drug and Therapeutics Committee (DTC) also plays an active leading role in the advancement of medicine safety and strengthening PV centers at the hospital [46].…”
Section: Discussionsupporting
confidence: 79%
“…These suggestions made by participants were almost similar to other studies in different hospitals in the world [25,30,38]. These suggestions were almost similar to other studies conducted in other countries which show that educational interventions and other activities help to encourage ADR reporting increase awareness to ADRs and then increase the reporting rates of ADRs [20,21,25,30,38,[43][44][45]. Drug and Therapeutics Committee (DTC) also plays an active leading role in the advancement of medicine safety and strengthening PV centers at the hospital [46].…”
Section: Discussionsupporting
confidence: 79%
“…Frequently, the pharmacist is in a unique position and plays more essential roles that include many pharmaceutical care aspects, such as evading medication errors and ADRs, promoting better Quality of Life (QoL), financial outcomes, and patient wellbeing. Varallo FR et al, study indicated that using MEIs with multidisciplinary teams including pharmacists for pharmacovigilance revealed a remarkable rise exceeding 100% in the absolute number of reports of drug-induced issues, increase in the prevalence of medication error reporting and increased the relevance of ADE reports [33]. It highlighted the importance of adopting a multidisciplinary perspective of approach for the importance of pharmacovigilance in adding to patient safety.…”
Section: Figure 3: Matched Pairs Difference Of Perception Post-intervmentioning
confidence: 99%
“…The results showed that the educational intervention was successful in the understanding of PV concepts, and improving skills to effectively complete reports related to ADRs. Directly after the educational intervention, the number of reports increased; however, four months after the educational intervention the number decreased, which implies that the education has to be continuous or periodic to keep the motivation among healthcare practitioners toward reporting ADRs 65 .…”
Section: Policies and Procedures For Implementing Pharmacovigilancementioning
confidence: 99%